2012
DOI: 10.1007/s10393-012-0785-3
|View full text |Cite
|
Sign up to set email alerts
|

Macroparasite Infections of Amphibians: What Can They Tell Us?

Abstract: Understanding linkages between environmental changes and disease emergence in human and wildlife populations represents one of the greatest challenges to ecologists and parasitologists. While there is considerable interest in drivers of amphibian microparasite infections and the resulting consequences, comparatively little research has addressed such questions for amphibian macroparasites. What work has been done in this area has largely focused on nematodes of the genus Rhabdias and on two genera of trematode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 157 publications
1
91
1
1
Order By: Relevance
“…In this system, free-living, parasitic trematode cercariae are transmitted from snails, the first intermediate host, to tadpoles, the second intermediate host (22) (see SI Background for a description of the life cycle) and several vertebrate and invertebrate taxa are known to consume cercariae (e.g., refs. 9 and 23-25; see SI Background for more details).…”
mentioning
confidence: 99%
“…In this system, free-living, parasitic trematode cercariae are transmitted from snails, the first intermediate host, to tadpoles, the second intermediate host (22) (see SI Background for a description of the life cycle) and several vertebrate and invertebrate taxa are known to consume cercariae (e.g., refs. 9 and 23-25; see SI Background for more details).…”
mentioning
confidence: 99%
“…Studies on pathology have focused on invertebrate intermediate hosts (Ruiz and Lindberg, 1989;Ituarte et al, 2001Ituarte et al, , 2005Huntley, 2007;Huntley and Scarponi, 2012;Huntley et al, 2014;Huntley and De Baets, 2015), although some pathologies in vertebrate intermediate hosts have also been linked with parasitic flatworms. The best examples are probably the teratological limb malformations in North American amphibians, which have been linked with the trematode Ribeiroia on several occasions (Johnson et al, 2001(Johnson et al, , 2002Stopper et al, 2002;Johnson and Sutherland, 2003;Johnson and Chase, 2004;Koprivnikar et al, 2012) and could potentially be found in the fossil record (cf . Fr€ obisch et al, 2014).…”
Section: Eocene Shell Pits In Intermediate Bivalve Hostsmentioning
confidence: 99%
“…Ongoing declines and deformities in amphibian populations have catalyzed increased interest in the effects of parasites and pathogens on amphibian ecology and conservation (Blaustein et al, 2012;Densmore and Green, 2007;Kilpatrick et al, 2010;Koprivnikar et al, 2012). Alongside habitat loss, climate shifts, and pollution, infectious diseases represent one of the most important threats confronting amphibians worldwide (Collins and Storfer, 2003;Lips et al, 2006;Stuart et al, 2004).…”
Section: Introductionmentioning
confidence: 99%